Effect of methyl methacrylate monomer on bond strength of denture base resin to acrylic teeth - Marra, Julie [UNESP]; Paleari, Andre Gustavo [UNESP]; Pero, Ana Carolina [UNESP] [UNESP]; de Souza, Raphael Freitas; Barbosa, Débora de Barros [UNESP]; Compagnoni, Marco Antonio [UNESP] (Elsevier B.V., 2009)
Bond failures at the acrylic teeth and denture base resin interface are still a common clinical problem in prosthodontics. The effect of methyl methacrylate (MMA) monomer on the bond strength of three types of denture base resins (Acron MC, Lucitone 550 and QC-20) to two types of acrylic teeth (Biotone and Trilux) was evaluated. Twenty specimens were produced for each denture base resin/acrylic tooth combination and were randomly divided into control (acrylic teeth received no surface treatment) and experimental groups (MMA was applied to the surface of the acrylic teeth for 180 s) and were submitted to shear tests (1 mm/mm). Data (MPa) were analyzed using three-way ANOVA/Student's test (alpha = 0.05). MMA increased the bond strength of Lucitone denture base resins and decreased the bond strength of QC-20. No difference was detected for the bond strength of Acron MC base resin after treatment with MMA. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Interfaces; Surface treatment; Adhesion